Epigenetic Contribution of High-Mobility Group A Proteins to Stem Cell Properties - Vincenzo Giancotti; Natascha Bergamin; Palmina Cataldi; Claudio Rizzi (International Journal of Cell Biology)
High-mobility group A (HMGA) proteins have been examined to understand their participation as structural epigenetic chromatin factors that confer stem-like properties to embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and cancer stem cells (CSCs). The function of HMGA was evaluated in conjunction with that of other epigenetic factors such as histones and microRNAs (miRs), taking into consideration the posttranscriptional modifications (PTMs) of histones (acetylation and methylation) and DNA methylation. HMGA proteins were coordinated or associated with histone and DNA modification and the expression of the factors related to pluripotency. CSCs showed remarkable differences compared with ESCs and iPSCs.